2020
DOI: 10.1002/pa.2505
|View full text |Cite
|
Sign up to set email alerts
|

Toward a new conceptualization of financial well‐being

Abstract: Research on financial well-being is still in its nascent stage, despite being an important topic in consumer research. Research on the antecedents of financial well-being is even more limited. Using in-depth interviews with consumers and practitioners, and expert discussions, this article conceptualizes the construct of financial wellbeing from underdeveloped countries' perspective. We conceive financial well-being as a confluence of four situations-namely, meeting present and future financial commitments; fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 79 publications
0
38
0
Order By: Relevance
“…In addition, career outlook was found to be related to financial well-being, and controlling the emotions in respect of the career outlook can result in the normalcy of behaviour. The importance of financial well-being in underdeveloped countries was also duly recognized by Mahendru et al (2020). Through LOGIT regression, we also found emotional resilience, social support, and avoidance to be the effective factors to control behaviour, and these were ranked as per the order of their occurrence, i.e.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, career outlook was found to be related to financial well-being, and controlling the emotions in respect of the career outlook can result in the normalcy of behaviour. The importance of financial well-being in underdeveloped countries was also duly recognized by Mahendru et al (2020). Through LOGIT regression, we also found emotional resilience, social support, and avoidance to be the effective factors to control behaviour, and these were ranked as per the order of their occurrence, i.e.…”
Section: Discussionmentioning
confidence: 77%
“…Financial self-efficacy based on "SCT and financial literacy" is the independent variable that promotes employee's FWB. Many authors have shown the significance of "financial literacy" for promoting "FWB" (Shim et al, 2009;Sabri et al, 2010;Mahendru et al, 2020). In Figure 10, KS may be a moderator connecting employees' "financial literacy" and "FWB.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…With savings rates at record lows and inadequate long-term financial planning for retirement (Taft et al, 2013), FWB has become an important topic for individuals and households as well as for societies and countries. Research on the topic, however, remains scarce and scattered across disciplines (Brüggen et al, 2017;Mahendru et al, 2020). There are very few researches on the aspects relating to how FWB aids an organization's employees (Choi et al, 2020;Sabri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The exception being the study conducted by Tach and Greene (2014)– the authors employed in‐depth interviews of 194 low‐income households to find interesting constructs, that is, promotion of self‐sufficiency in social identity, upward mobility in societal ladder and private coping strategies, to achieve consumer FWB. Another qualitative research explored the meaning and context of FWB in both objective and subjective sense in India (Mahendru et al., 2020). More qualitative studies in the area will provide fresh insights to develop newer constructs by subsequent quantitative studies or to explain the meanings, social norms, and behaviors of consumers in developing nations–an area that we know so little about.…”
Section: Methodological Rigor In Financial Well‐being Researchmentioning
confidence: 99%